KEBUTUHAN TOKOH DALAM NOVEL SEPERTI HUJAN YANG JATUH KE BUMI KARYA BOY CANDRA - Elga Ayuditya Yahdiyani; Sumiman Udu; Sri Suryana Dinar; Andi Muhammad Ruum Sya'baan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to describe the needs of the characters in the novel Seperti Hujan yang Jatuh Ke Bumi by Boy Candra based on the perspective of Abraham Maslow's humanistic psychology. The type of research used is library research and the method used is a qualitative descriptive method. In this study, the data used are words, sentences, complete paragraphs and quotations that describe the needs of the characters in the novel Seperti Hujan yang Jatuh Ke Bumi by Boy Candra, using Abraham Maslow's humanistic psychology theory. The data collection technique in this study is the analytical intensive reading technique and the note-taking technique. The data analysis technique used is to focus on revealing and understanding more deeply about humanistic psychology involving the characters of the characters. The results of the study show that the four main characters in the novel Seperti Hujan yang Jatuh Ke Bumi, namely Kevin, Nara, Juned and Tiara have needs that can be divided into two categories, namely physiological needs and psychological needs. According to Maslow, these needs are the basis of human behavior that drives individuals to achieve personal goals and happiness. This study provides insight into the relationship between character psychology in literary works and Maslow's theory of needs, as well as its relevance in literary learning.